Abnormal returns for codeshare agreements and frequent flyer programme cooperation. - Low, Alicia Su Ru. (2013)
This paper looks into the stock market reaction to the announcements of airline alliances, more specifically codeshare agreements and frequent flyer programme (FFP) cooperation. We conducted an event study to measure the changes in returns within a 5-day event window of the date of announcements and found that there were no positive abnormal returns following announcements of codeshare agreements alone. Also, upon further analysis, we found that network-based codeshare agreements did not generate greater abnormal returns than route-based codeshare agreements. However, as hypothesized, our results showed that announcements of FFP cooperation did receive positive stock market reaction. The results revealed that that there were marginally significant positive abnormal returns following announcements of alliances consisting of both codeshare agreement and FFP cooperation. The abnormal returns following such announcements were also significantly greater than announcements of codeshare agreements only. We also recategorized the announcements by size of airline (in terms of passenger traffic), as well as regions to find out which sub-categories contributed to our results.